Combining matrix design for 2D DoA estimation with compressive antenna arrays - Lavrenko, A.; Pawar, S.; Ibrahim, M.; Römer, F.; Del Galdo, G.; Thomä, R. S. (WSA 2018 - 22nd International ITG Workshop on Smart Antennas, 2018)
In this paper, we develop an approach for a combining matrix design for 2D DoA estimation with compressive arrays. In compressive arrays, a (larger) number of antenna outputs is linearly combined to a lower number of receiver channels with the aim to reduce hardware complexity while not compromising the estimation performance. To achieve this goal, we base our design on the antenna's spatial correlation function (SCF) in an attempt to provide an effective compressive array whose estimation capabilities are close to those of the original array before the combining. Due to the need to consider the SCF in both azimuth and elevation, the size of the resulting optimization problem becomes prohibitive. Therefore, we propose a reduced-size design that takes advantage of the SCF change rates in azimuth and elevation. We evaluate the proposed approach numerically, which demonstrates that it allows us to achieve a significant complexity reduction while providing satisfactory DoA estimation performance.
CRIS-Team Scopus Importer:2025-11-10